Exploring the Geographic Consequences of Public Policies Using Evolutionary Algorithms. - Bennett, David A.; Xiao, Ningchuan; Armstrong, Marc P. (Annals of the Association of American Geographers, 2004)
The writers present a technique based on an evolutionary algorithm (EA) that generates a large number of optimal and near-optimal solutions to a broad range of land management problems. As a context to their new technique, they explore the effect of the U.S. Department of Agriculture's Conservation Reserve Program on rural landscapes. They assume three objectives: maximize farm income, maximize environmental quality, and minimize public investment in conservation programs. They develop analytical and visualization tools to lessen the burden associated with exploring the large number of solutions that are produced by this method. They reveal that the EA-based approach can generate results equal to and significantly more diverse than conventional integer programming techniques.